Edukasi Perencanaan Dana Pensiun secara Mandiri Bagi Karyawan Swasta SMK Terpadu Putra Jaya Batam - Widya Reza; Andini Setyo Anggraeni; Sabarinsyah (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: One of the phenomena surrounding Indonesian society is the lack of awareness of pension fund planning, so there are often financial problems in retirement. This activity aims to educate the public about the importance of independent pension fund planning, especially private employees. Method: This activity was carried out at SMK Terpadu Putra Jaya Batam with 25 participants. This activity lasted for six weeks, with the intervention providing education on pension fund planning and calculating pension fund needs independently. This series of activities consists of a pretest, material description, discussion session, and post-test. Results: This activity increased participants' understanding of the importance of independent pension fund planning for private employees. The pretest results showed that participants who understood and were interested in planning pension funds only amounted to 5%. The post-test results showed that 98% of participants understood and intended to prepare pension funds. Participants also learned about calculating the time value of money for pension funds and choosing suitable investments. Conclusion: The participants were very enthusiastic about participating in this activity which was shown by an increased understanding and interest in planning pension funds independently. Even though they already have high knowledge, private employees should also be able to control themselves to have good retirement fund planning.